Orwell on Kipling: an imperialist, a gentleman and a great artist - Ferreira, Júlio Carlos Viana (2017)
Eric Arthur Blair, later known by his pen name George Orwell, was born in 1903 in India, attended Eton College from 1917 to 1921, and served the Indian Imperial Police in Burma for five years until he resigned in 1928, due to a feeling of overwhelming revulsion and an intense loathing of the imperialism of which he had been a part. Thus, it was Orwell, the anti-imperialist and radical socialist who, despite strongly disapproving of both Kipling’s alleged jingo imperialism and his moral insensitiveness, acknowledged that Kipling behaved like a gentleman throughout his life and, by creating memorable catch-phrases of general use, had a streak of genius (CW 410). It is this complex picture of Kipling’s work and personality, as sketched by Orwell, which this essay will explore.